Calcium: Alpha-Synuclein Interactions in Alpha-Synucleinopathies - Rcom-H'cheo-Gauthier, Alexandre N.; Osborne, Samantha L.; Meedeniya, Adrian C. B.; Pountney, Dean L. (Frontiers in Neuroscience, 2016)
Aggregation of the pre-synaptic protein, α-synuclein (α-syn), is the key aetiological factor in Parkinson’s disease (PD) and other alpha-synucleinopathies, such as multiple system atrophy and Dementia with Lewy bodies. Various triggers for pathological α-syn aggregation have been elucidated, including port-translational modifications, oxidative stress and binding of metal ions, such as calcium. Raised neuronal calcium levels in PD may occur due to mitochondrial dysfunction and/or may relate to calcium channel dysregulation or the reduced expression of the neuronal calcium buffering protein, calbindin-D28k. Recent results on human tissue and a mouse oxidative stress model show that neuronal calbindin-D28k expression excludes α-syn inclusion bodies. Previously, cell culture model studies have shown that transient increases of intracellular free Ca(II), such as by opening of the voltage-gated plasma calcium channels, could induce cytoplasmic aggregates of α-syn. Raised intracellular free calcium and oxidative stress also act cooperatively to promote α-syn aggregation. The association between raised neuronal calcium, α-syn aggregation, oxidative stress and neurotoxicity is reviewed in the context of neurodegenerative α-syn disease and potential mechanism-based therapies.